GW24-e3611 Autoantibodies against the cardiac beta1-adrenergic-receptor in patients with diastolic dysfunction after acute myocardial infarction. (1st October 2013) - Shan, He; Shanshan, Zhai
Abstract : Objectives: Autoantibodies against the cardiac beta1-adrenergic-receptor were found in serum from heart failure patients with different cardiac diseases. While according to echocardiography, most of the patients had systolic heart failure. There were no relative researches on diastolic dysfunction. To determine whether the autoantibodies against the cardiac beta1-adrenergic receptors are related to diastolic dysfunction after acute myocardial infarction. Methods: 109 cases with acute myocardial infarction were admitted from September 2012 to January 2013. Synthetic peptides corresponding toamino acids sequence of the second extracelluar loops of the beta1-adrenergic-receptor were used as the antigens to detect the serum levels of autoantiboides from the patients after acute myocardial infarction by means of enzyme linked immune assay. Meanwhile cardiac function was examined by echocardiography within 48 hours after admission and NT-pro BNP was detected. Results: According to the cardiac function by echocardiography, the patients were divided into three groups. Patients in group 1 have normal cardiac function, group 2 with diastolic dysfunction and group 3 with systolic dysfunction. The positive rates of serum autoantibodies for beta1-adrenergic-receptor were 24.2% (8/33) in group 1, 33.3% (17/51) in group 2 and 46.4 (13/28) in group 3 respectively (P > 0.05). Conclusions: Our finding indicates that autoantibodies against beta1-adrenergic-receptor is found not only in the serum of systolic dysfunction patients but also in patients with diastolic dysfunction after myocardial infarction although there is no significant difference compared with patients with normal cardiac function. So we need more cases to confirm whether beta1-adrenergic-receptor autoantibodies are related to diastolic dysfunction and its mechanism.